Rancang Bangun Media Pembelajaran pada Mata Pelajaran Sistem Pemograman Berbasis IoT Kelas XI di SMK Negeri 1 Pariaman Berbasis Android Menggunakan Smart App Creator - Rizka Amanda; Yasdinul Huda; Vera Irma Delianti; Rido Putra (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to develop an interactive learning media based on android using a valid and practical smart app creator to improve students' understanding of the SPBI course in the Industrial Automation Engineering Department of SMK Negeri 1 Pariaman. This study uses the Research and Development (R&D) method with the ADDIE model as a guideline in the development process. The results of this study provide evidence that the interactive learning media created falls into the "Valid" category. This is proven based on validation carried out by material experts with a validity value of 87% (0.870) and validation carried out by media experts with a validity value of 92.11% (0.921). Furthermore, a Media Practicality Test was carried out by class XI students of SMK Negeri 1 Pariaman with a practicality value of 91.60% (0.961) falling into the Very Practical category.